Perceptions of nursing home workers, police chiefs, and college students regarding crime against the elderly: An exploratory study - Payne, Brian K. (American journal of criminal justice, 1999)
The growing elderly population means that crime will play a larger role in future quality of life issues. Even so, few criminal justice endeavors have examined how different actors perceive various aspects of elderly victimization. This paper examines the way four distinct groups—nursing home directors, nursing home employees, police chiefs, and university students—perceive crime against the elderly. Results show nursing home professionals perceive aspects of elderly victimization differently than do police chiefs and college students. Implications are provided.